Niveles de caries dental en niños con y sin discapacidad en dos centros educativos primarios estatales de Iquitos 2024 - Torres Torres, Teddy Junior (2024)
OBJECTIVE: To compare the levels of dental caries among children aged 8 to 11 years with and without disabilities from two state schools in Iquitos, 2024. METHODOLOGY: The present study is quantitative, non-experimental, comparative, cross-sectional and prospective. For this study, a sample of 222 children between 8 and 11 years of age was divided into two educational centers, 50 in the C.E.B.E. Iquitos and 172 in the I.E.P Eleodoro Bustamante López, in the city of Iquitos, Peru. A dental chart with the CPO-D index was used as an instrument. RESULTS: The average CPO-D index was 1.54, reflecting the general state of oral health in children aged 8 to 11 years. Regarding the distribution of CPO D levels, 48.6% (n=108) had a low level, which represents the majority of the evaluated population. 37.4% (n=83) showed a very low level. Finally, 14.0% (n=31) of the cases presented a moderate level, indicating that a smaller group of the sample would require greater attention. CONCLUSION: In conclusion, the data obtained show that children with disabilities have lower levels of dental caries compared to children without disabilities, due to the fact that their parents and caregivers have a more careful approach due to their different health problems.